A comparative study of the effect of the gradient term type on the plasticity solution behaviour - Lyamina, Elena Alexeevna (Computational Continuum Mechanics, 2009)
The effect of the type of correction functions on the solution behavior is studied within the framework of the theory of gradient plasticity. Two ways of gradient term representation are considered, of which one uses a conventional form, and the other suggests application of space derivatives of the equivalent strain rate. Attention is mainly devoted to the difference in the qualitative behavior of the solutions of the boundary value problem on expansion of a sphere having an inner cavity of small radius acting as a stress concentrator. It is shown that the solution based on the new correction function better corresponds to physical expectations concerning the effect of the gradient term on the solution behavior.